COMPARATIVE STUDY ON DISCOURSE ANALYSIS IN SCHOOLS’ SLOGAN - Natalia Monica Masela (JURNAL TAHURI, 2018)
The aim of this research is to know what kind of speech act meaning shown in fifteen school slogans. This research is descriptive qualitative research. The subject of this research is school slogan that be used in three different schools, there are SD Negeri 2 Ambon, SMP Negeri 3 Leihitu and SMP Santo Andreas Ambon. The fifteen slogans consist of five Indonesian slogan and ten English slogan. In finding out the kind of speech act meaning, the researcher used semantic analysis, in this case used speech act analysis. The result showed that there are five kinds of speech act meaning shown in fifteen slogans. Those fifteen slogans are divided into four slogans in representative meanings, five slogans in directive meanings, two slogans in commisive meanings, two slogans in expressive meanings and two slogans in declarative meanings. Then, both English and Indonesian slogan can be classified in all meaning of speech act. Besides, most of school slogan is using directive and representative meaning of speech act.